2019
DOI: 10.1007/s10147-019-01546-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of capecitabine plus oxaliplatin (CapOX) as adjuvant chemotherapy for locally advanced rectal cancer (CORONA II)

Abstract: Objective This multicenter, single-arm phase II study (UMIN000008429) aimed to evaluate the efficacy and safety of capecitabine plus oxaliplatin (CapOX) as postoperative adjuvant chemotherapy for patients with locally advanced rectal cancer. Methods Patients with resectable clinical Stage II or III rectal cancer were enrolled to receive eight cycles of CapOX therapy (130 mg/m2 oxaliplatin on day 1 and 2000 mg/m2 oral capecitabine on days 1–14, every 3 weeks) after curative surgical resection. The primary end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…They proposed that the trophic effect of gastrin over gastric mucosa could induce the development of gastric adenocarcinoma. Also, Yanagawa et al [ 19 ] proposed that immunosuppression induced by a lymphoma could lead to the development of adenocarcinoma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that the trophic effect of gastrin over gastric mucosa could induce the development of gastric adenocarcinoma. Also, Yanagawa et al [ 19 ] proposed that immunosuppression induced by a lymphoma could lead to the development of adenocarcinoma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the SPS group, diverting ileostomy was performed as appropriate, which was reversed 3-4 months after surgery or after administration of adjuvant chemotherapy. Neoadjuvant chemotherapy was given for some stage II/III patients as a part of our clinical trial or daily practice [15,16], whereas preoperative chemoradiotherapy (CRT) was indicated for limited patients when the radial margin was involved after neoadjuvant chemotherapy [17].…”
Section: Treatmentmentioning
confidence: 99%
“…On the contrary, FOLFOX requires hospitalising the patient for 4 days per course, raising its cost. However, unsupervised outpatient CTx with capecitabine involves a risk of irregular treatment and can be inappropriate for some patients, leading to worse outcomes [19][20][21]. Administering SCRT requires specialised techniques, such as IMRT or VMAT, which costs less, and there is no marked difference between them.…”
Section: (Continued)mentioning
confidence: 99%